LO097: A novel curriculum for assessing competency in resuscitation at the foundations of discipline level of training. (2nd June 2016) - Chaplin, T.; McMurray, L.; Hall, A.K.
Abstract : Introduction / Innovation Concept: Junior residents are often the first physicians who attend to the acutely unwell floor patient, especially at night and on weekends. The 'Nightmares Course' at Queen's University was designed to address an Entrustable Professional Activity (EPA) relevant to several residency programs at the 'Foundations of Discipline' level of training: "to manage the acutely unwell floor patient for the first 5-10 minutes until help arrives". In keeping with competency based medical education principles, this course offers longitudinal and repetitive practice and assessment. We have also designed a summative objective structured clinical exam (OSCE) in order to identify trainees who require additional remedial practice of this EPA.Methods: We developed simulated cases that reflect common but "scary" calls to the floor. We then, using a modified Delphi process with experts in resuscitation, defined relevant milestones applicable to the Foundations of Discipline level of training in order to inform our formative assessment. We also modified the Queen's Simulated Assessment Tool (QSAT) to adopt CBME terminology and this will be used to provide a summative assessment during a four-scenario OSCE in the spring. Residents with QSAT scores below the competency threshold will be enrolled in a remediation course.Curriculum, Tool, or Material: Weekly sessions were led by staff physicians and were offered to first-year residents from internal medicine, core surgery, obstetrics and gynecology, and anesthesiology over the academic year. Each resident participated in one session every 4-week block. Sessions were organized into themes such as "shortness of breath" or "decreased level of consciousness" and involved three high-fidelity simulated cases with a structured debrief following each case. Formative feedback was given following each case.Conclusion: The Nightmares Course is a novel simulation-based, multidisciplinary curriculum in resuscitation medicine. It includes longitudinal practice and repetitive assessment, as well as summative testing and remediation of an EPA common to several residency programs.